The Prognostic and Therapeutic Significance of T-Helper-1 Cell Response in Patients with Severe Systemic Inflammatory Response or Sepsis - Cabioglu, Neslihan; Akta?, Esin Çetin; Gazio?lu, Sema Bilgiç; Kiran, Bayram; Günay, Kayhan; Ertekin, Cemalettin; Gülo?lu, Recep; Ak?nc?, Muzaffer; Deniz., Günnur (Archives of Clinical and Biomedical Research, 2025)
Background/Objectives: Severe sepsis/multiorgan failure is the cause of 50 to 80% of all deaths in surgical intensive care units. The aim of the present study is to study peripheral lymphocyte subsets and identify the immunomodulatory role of in vitro effect of IL-12 on interferon-gamma secreting lymphocytes in severe surgical sepsis who were treated in intensive care unit (ICU). Methods: Patients with either severe systemic inflammatory response (SIRS) or surgical sepsis who were treated at the ICU, were included into the study. Blood samples were analyzed to estimate peripheral blood leucocyte (PBL) and T-helper lymphocyte subsets by flow cytometry. The in vitro effect of IL-12 on IFN-gamma secreting PBLs and cytokine levels were studied using specific kits. Results: The 28-day survival rate was 50% (7/14), whereas the overall survival rate was 28.5% (4/14). The median APACHE II, SOFA and MARSHALL MOD scores were 23 (range, 14-27), 7 (2-12) and 7 (2-11), respectively. In 28-day survival analysis, CD56+ cell populations were decreased in nonsurvivors (p=0.05), whereas T-gamma delta+ and CD3+HLADR+ cells were statistically diminished in patients with higher SOFA scores (p=0.032, and p=0.019, respectively) associated with poor outcome. In correlation analyses, CD3+ cell ratios were positively correlated with APACHE II and MOD scores (p=0.025 and p=0.047), whereas CD3+HLADR+ cells and T-gamma delta+ cells have shown negative correlations with SOFA scores (p=0.03 and p=0.01, respectively). In vitro culture assays with IL-12 stimulation of PBLs have shown that the total IFN-gamma secreting cells and their subsets could be significantly modulated upon peptide stimulation according to their median values. Furthermore, IL-12 enhanced IFN-gamma and IL-12 levels in either stimulated or unstimulated culture supernatants (p=0.025 and p=0.046 for IFN-gamma, p=0.028 and p=0.007 for IL-12).” Conclusions: Our results suggest that IL-12 modulates antigen spesific IFNgamma secreting cells and IFN-gamma levels in patients with severe sepsis or severe SIRS in ICU. The prognostic significance of CD56+ and T-gamma delta+ cells in sepsis and whether IL-12 could be used for therapeutical purposes in severe septic patients should be studied in future clinical studies.